Nutrient Analysis, Phytochemical and Antioxidant Activity of a Food Product Formulated with Fox Nuts (Euryale ferox) - Joseph, Amanda; Ramesh, Gowri (Asian Journal of Biological and Life Sciences)
Aim/Background - Fox nuts (Euryale ferox), a South Asian native crop, are found to be high in protein and micronutrient content and are shown to have antioxidant, hypocholesterolemic, and anticarcinogenic properties. Materials and Methods - The purpose of this research was to formulate an energy and nutrient-dense food product using fox nuts as the primary ingredient along with almonds, dates, flax seeds, and clarified butter. An ethanolic extract of the product was used to carry out qualitative phytochemical analysis and antioxidant assays. Results: 100 g of the formulated product was found to have 485 Kcal of energy, 10.7 g of protein, 27.7 g of total fat, 48.3 g of carbohydrate, 15.5 mg of iron, and 133.3 mg of calcium. The presence of phenols, flavonoids, alkaloids, terpenoids, tannins, and glycosides was detected in the formulated product. IC50 value of the product obtained via DPPH● assay was 55.43 μg/mL indicating strong antioxidant activity. The reducing power of the product via FRAP and Phosphomolybdenum assays were found to be 2.08 and 2.03 respectively at the highest concentration of 120 μg/mL. Conclusion: Data from the present study showed that the formulated product had a good nutrient profile and free radical scavenging potential.
Keywords: Antioxidant; Fox nuts; Nutrient profile; Phytochemicals